Proportional Representation and its Impacts on Multi Ethnic Society of Sri Lanka - Aliff, Seeni Mohamed (International Research Journal of Management, IT & Social Sciences, 2016)
This paper will examine the impact of PR electoral systems in a divided society. This research will explore the strength and weakness of the current electoral system and institutional design of Sri Lanka and will recommend changes to decrease the risk of minority exclusion in decision making and ethnic violence. The objectives of this research are to examine the character of the merits and demerits of the PR, and to investigate and assess the impacts of the PR in the multi ethnic societies of Sri Lanka. The study is a qualitative case study, and primary and secondary data sources have been employed to gather relevant data. The My Fieldwork was conducted in Sri Lanka, with the intention of gaining a better and more thorough understanding of the current situation. The interviews conducted were as such not structured or semi-structured, due to the intervieweesâ varying professional background and institutional affiliation. Accordingly, unstructured interviews, as well as informal conversations and meetings, were conducted throughout Sri Lanka.